The The Effect of Holy Quran Recitation on Clinical Outcomes of Patients Undergoing Weaning from Mechanical Ventilation - Elcokany, Nermine M.; Abd El Wareth, Mona Saad (International Journal of Innovative Research in Medical Science, 2019)
Background: Mechanically ventilated patients experience many stressors related to their physiological conditions, treatments, and the Intensive Care Unit (ICU) environment itself. As patients are recovered from the respiratory problems, they can be weaned from mechanical ventilation (MV). Weaning represents a major challenge in critically ill patients' management. Weaning from MV imposes more stress on the patients as it leads to feeling of helplessness. Excessive and inappropriate use of sedatives can result in cardiovascular instability, prolongation of MV and ventilator associated pneumonia. Critical care nurses have an important role in alleviating stress manifestations and helping patients’ holistic healing. Non-pharmacological approach is recommended to be used prior to or in conjunction with sedatives use. Listening to Holy Quran Recitation (HQR) is a kind of spiritual support for Muslim patients. Spiritual care has been recommended as it can affect patient’s comfort. Accordingly, spiritual support strategies including HQR have been recently proposed to achieve better outcomes of critically ill patients which is the aim of the current study. Methods: A quasi experimental research design was used in this study. Physiological and psychological parameters were measured before and after HQR in the study group. Results: All differences between physiological and psychological parameters of the study group before and after HQR were statistically significant (P= 0.00). All differences between initial and the final measurement values of physiological and psychological parameters of the control group were statistically not significant. The mean values of heart rate, respiratory rate, mean arterial blood pressure, and shortness of breath of the study group after HQR were lower than that in the control group. Conclusion: HQR is an effective non-pharmacological strategy to improve vital signs, SpO2, shortness of breath and anxiety level for mechanically ventilated Muslim patients undergoing weaning. In addition, it can increase spontaneous breathing trial (SBT) duration for patients undergoing weaning from MV.